Propylene metathesis with rhenium oxide supported by gamma alumina as catalyst including kinetic and initial reaction [mirofilem ] - 313852 Hsu, Chun-Chin (Ann Arbor, MI : UMI, 1980)
Thesis (PhD)- University of Oklahoma, 1980